Indonesia PENGARUH KUALITAS LAYANAN, KEAMANAN DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH PENGGUNA OLLIN BY NAGARI DI KABUPATEN TANAH DATAR - Annisa (Program Studi Ekonomi Islam - UIN Sjech M. Djamil Djambek Bukttinggi, 2025)
Technological developments have had a significant impact on the banking industry, driving innovation in financial services. Bank Nagari Syariah launched the Ollin by Nagari Mobile Banking application to meet the needs of digital-era customers. Despite offering convenience, customer complaints regarding service quality, security, and trust still arise. This study analyzes the factors influencing customer loyalty to the Ollin by Nagari application using a quantitative associative method. A population of 2,612 customers was sampled with 96 respondents using the Slovin formula. Primary data from questionnaires and secondary data were processed using multiple linear regression. The results show: service quality has a significant positive partial effect (sig. 0.001 < 0.05), security (0.014 < 0.05), and trust (0.009 < 0.05). The simultaneous F ujit shows that all three have a significant positive effect on customer loyalty in Tanah Datar Regency. This finding indicauji that improving service quality and security can increase loyalty. The study provides input for Bank Nagari Syariah to improve services, secure applications, and build customer trust.